2005
DOI: 10.1136/adc.2003.048165
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of an association between MMR vaccine and gait disturbance

Abstract: Background: MMR vaccine has been reported to cause gait disturbance, and this possible association has been claimed to support the MMR-causes-autism theory. Aims: To determine whether any association between gait disturbance and MMR vaccination exceeds the age related background rate of gait disturbance, using record linkage and self control case series analyses. Methods: MMR vaccination records were linked to hospital admission and general practitioner attendance data. An increased rate of gait problems with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Previous passive surveillance suggested a temporal relationship between MMR and increased ataxia, 37 whereas a more recent self-controlled case series analysis found no association between gait disturbances and MMR. 38 Overall, the Institute of Medicine concluded that the evidence was "insufficient or absent to assess an association between MMR vaccine and ataxia." 14 Although it is theoretically possible that both vaccines offer protection against ataxia, we instead favor the interpretation that this observation is more likely due to chance, outcome misclassification, or other unmeasured confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous passive surveillance suggested a temporal relationship between MMR and increased ataxia, 37 whereas a more recent self-controlled case series analysis found no association between gait disturbances and MMR. 38 Overall, the Institute of Medicine concluded that the evidence was "insufficient or absent to assess an association between MMR vaccine and ataxia." 14 Although it is theoretically possible that both vaccines offer protection against ataxia, we instead favor the interpretation that this observation is more likely due to chance, outcome misclassification, or other unmeasured confounding.…”
Section: Discussionmentioning
confidence: 99%
“…They also confirm the need to replicate single reports which have suggested a problem when a new therapy is introduced, with robust systems like our active surveillance system, which has been developed to assess possible adverse events following vaccination and has proved capable of providing a rapid, reliable response to possible vaccine scares 3ā€“6 8 9…”
Section: Discussionmentioning
confidence: 54%
“…All MMR vaccinations were followed up for 60 days which allowed comparing vaccinated with non-vaccinated children. According to Miller et al: "this study provides no evidence that MMR vaccine causes acute ataxia or other gait disturbance and suggests that the cases originally described by Plesner were chance occurrences, reflecting background incidence" [113].…”
Section: Health Authorities Might Not Take Note Of This Adverse Reactmentioning
confidence: 77%